Lateral Lymph Node Metastases in Locally Advanced Low Rectal Cancers May Not Be Treated Effectively With Neoadjuvant (Chemo)Radiotherapy Only - Haanappel, Anouck; Kroon, Hidde M.; Schaap, Dennis P.; Bedrikovetski, Sergei; Dudi-Venkata, Nagendra N.; Lee, Hong X.; Thomas, Michelle L.; Liu, Jianliang; van der Valk, Maxime J. M.; Rutten, Harm J. T.; Beets, Geerard L.; Kusters, Miranda; et al. (Frontiers in Oncology, 2019)
Background: In the West, pre-treatment abnormal lateral lymph nodes (LLN+) in patients with a low locally advanced rectal cancer (AJCC Stage III), are treated with neoadjuvant (chemo)radiotherapy (nCRT), without a lateral lymph node dissection (LLND). It has been suggested, however, that LLN+ patients have higher local recurrence (LR) rates than similarly staged patients with abnormal mesorectal lymph nodes only (LLN-), but no comparative data exist. Therefore, we conducted this international multi-centre study in the Netherlands and Australia of Stage III rectal cancer patients with either LLN+ or LLN- to compare oncological outcomes from both groups. Material and Methods: Patients with Stage III low rectal cancer with (LLN+ group) or without (LLN- group) abnormal lateral lymph nodes on pre-treatment MRI were included. Patients underwent nCRT followed by rectal resection surgery with curative intent between 2009 and 2016 with a minimum follow-up of 2-years. No patient had a LLND. Propensity score matching corrected differences in baseline characteristics. Results: Two hundred twenty-three patients could be included: 125 in the LLN+ group and 98 in the LLN- group. Between groups, there were significant differences in cT-stage and in the rate of adjuvant chemotherapy administered. Propensity score matching resulted in 54 patients in each group, with equal baseline characteristics. The five-year LR rate in the LLN+ group was 11% vs. 2% in the LLN- group (P=0.06) and disease-free survival (DFS) was 64% vs. 76%, respectively (P=0.09). Five-year overall survival was similar between groups (73% vs. 80%, respectively; P=0.90). Conclusions: In Western patients with Stage III low rectal cancer, there is a trend towards worse LR rate and DFS rates in LLN+ patients compared to similarly staged LLN- patients. These results suggest that LLN+ patients may currently not be treated optimally with nCRT alone, and the addition of LLND requires further consideration.